Kegiatan Humas Indonesia Bergerak Di Kantor Pos Depok II Dalam Meningkatkan Citra Instansi Pada Publik Eksternal - susilowati susilowati (Universitas Bina Sarana Informatika, 2017)
A company at the time of its inception until its development can not be separated from the interaction process built with various parties. Relationships built within the enterprise can be encompassed in all walks of life and not only concerning the internal interests of owners and employees, but further the presence of companies intended to meet the needs of the wider community outside the enterprise. One of the tasks and functions of Public Relations in a company or agency is to improve the positive image. PT Pos Indonesia (Persero) has done various forms of postal services to the public, but often people do not give optimal assessment and still many complaints against the performance of PT Pos Indonesia (Persero), so one way to fix it is to create a program of PR activities and one of them is Indonesia Bergerak activity. The purpose of this research is to know the activities of Humas Indonesia Bergerak at PT Pos Depok II branch in improving the image of the institution in its external public. The author uses descriptive-qualitative research method, which is done by observation and in-depth interviews directly, and the data collected and then analyzed descriptively in the form of research reports. The conclusion of the results of this study is the